Filosofi Canang Sari Sebagai Simbol Padma Astadala - Kadek Juli Rismawati; Kadek Fina Cahyuni (Pramana: Jurnal Hasil Penelitian, 2023)
"Canang Sari," a distinctive flower offering in Balinese culture, holds profound significance as a symbol of Padma Asta Dala. Within the concept of Padma Asta Dala, each petal of the lotus represents essential aspects in the pursuit of spiritual balance. This article elaborates on the close relationship between Canang Sari and this concept, revealing how the arrangement and elements of Canang Sari reflect the symbolism of Dharma (duty), Adharma (disobedience), Lobha (greed), and Parama (perfection). Canang Sari serves as a potent visual reflection of life philosophy and spiritual quest in Balinese culture. This study employs qualitative observation and document analysis, with the author immersing themselves in the field. Through Canang Sari, the Balinese community immortalizes and celebrates harmony between humans, nature, and the divine. This article provides insights into the symbolic and practical significance of Canang Sari as a representation of the Padma Asta Dala concept in daily Balinese life. Despite the passage of time, Canang Sari remains a robust cultural symbol. As a manifestation of Padma Asta Dala, Canang Sari guides the Balinese people in seeking life harmony, conquering emotional challenges, and attaining inner peace. In every carefully arranged flower and leaf, a deeper spiritual message is unveiled, uniting nature, spirit, and the divine. Canang Sari not only adorns the corners of sacred places but also radiates symbolic meaning, teaching that balance is the key to achieving perfection in the spiritual journey.